The ESG Paradox in ASEAN Islamic Banking: Evidence From ESG Performance - Muslimin Muslimin; Sri Hasnawati; Mahatma Kufepaksi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study examines the ESG paradox in ASEAN Islamic banking, where Shariah compliance does not guarantee superior sustainability performance. Using pooled data from 53 listed banks across six ASEAN countries (2015 – 2024), the research analyses the determinants of ESG performance through pooled OLS regression with HAC estimators. Findings reveal an "ESG Paradox": Islamic finance presence shows no significant positive effect on aggregate ESG scores and shows a marginally negative association with environmental performance in the moderation model. Community engagement consistently drives all ESG pillars, while business ethics policies unexpectedly weaken the community-environment relationship. The study introduces "symbolic ESG" as a theoretical framework, highlighting that Shariah certification often serves as reputational veneer rather than substantive ethical driver. These findings urge regulators to harmonize Shariah audit standards, strengthen SSB independence, and mandate environmental disclosures, while stakeholders should avoid equating religious labels with ethical substance to sustain faith-based trust and prevent governance failures.